John Steinbeck holding a sextant. - Wieskaw Ksiazek:::Creator::::::::::::
John Steinbeck holding a sextant, possibly in the Copernicus Room of Collegium Maius (established 1400), historical seat of Jagiellonian University in Poland. (Krakow University).Original photograph is in the safe.